2005
DOI: 10.1080/02640410410001730151
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of resistance exercise on the main determinants of blood rheology

Abstract: The aim of this study was to examine short-term changes in blood rheological variables after a single bout of resistance exercise. Twenty-one healthy males completed three sets of 5 - 7 repetitions of six exercises at an intensity corresponding to 80% of one-repetition maximum (1-RM). The average duration of the exercise bout was 35 min. Venous blood samples were obtained before exercise, immediately after exercise and after 30 min of recovery and analysed for lactate, red blood cell count, haematocrit, haemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
56
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 25 publications
9
56
2
Order By: Relevance
“…after the SRE is related the replenishment of the plasma volume (TEIXEIRA et al, 2014) especially after post-exercise hydration. The increase in the parameters two hours after exercise is more evident and derives from the systemic inflammatory response and we believe that these results best reflect musculoskeletal inflammation, since hemoconcentration has been reversed (AHMADIZAD; EL-SAYED, 2005;TEIXEIRA et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…after the SRE is related the replenishment of the plasma volume (TEIXEIRA et al, 2014) especially after post-exercise hydration. The increase in the parameters two hours after exercise is more evident and derives from the systemic inflammatory response and we believe that these results best reflect musculoskeletal inflammation, since hemoconcentration has been reversed (AHMADIZAD; EL-SAYED, 2005;TEIXEIRA et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of neutrophils during exercises may be related to many factors, such as muscular damage, hormonal factors and IL6 (PEAKE; SUZUKI, 2004). We emphasize that the period of 2 hours after SRE coincided with the peak concentration of inflammatory markers and the resulting neutrophilia (VELLA et al, 2012), once the hemoconcentration has already been reverted (AHMADIZAD; EL-SAYED, 2005). Nikolaidis et al (2008) suggested that the oxidative stress in blood and muscular tissues may manifest and persist for several days after the exercise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations